Therapeutic Effects of Slow Deep Breathing on Cardiopulmonary Function, Physical Performance, Biochemical Parameters, and Stress in Older Adult Patients with Long COVID in Phayao, Thailand - Tichanon Promsrisuk; Arunrat Srithawong; Ratchaniporn Kongsui; Napatr Sriraksa; Sitthisak Thongrong; Chiraphat Kloypan; Nattha Muangritdech; Kit Khunkitti; Thanakorn Thanawat; Petcharaporn Chachvarat (Annals of Geriatric Medicine and Research)
Background Long coronavirus disease (COVID) poses significant challenges for older adult patients, affecting their cardiopulmonary function and overall well-being. This study aimed to investigate the effects of slow deep breathing exercises on cardiopulmonary function, physical performance, biochemical markers, oxidative stress, and stress levels in older adult patients with long COVID. Methods Sixty older adult patients with long COVID were randomly assigned to an exercise group of 30 patients and a control group of 30 patients. The exercise group engaged in slow deep breathing exercises for 30 minutes, five times a week over a period of 8 weeks, while the control group maintained their usual activities. Cardiovascular parameters, heart rate variability (HRV), respiratory muscle strength (RMS), pulmonary function tests (PFT), physical performance, biochemical and oxidative stress markers, and stress levels were assessed at baseline, 4 weeks, and 8 weeks. Data were analyzed using one-way repeated measures ANOVA. Results The exercise group showed significant reductions in cardiovascular parameters (systolic and diastolic blood pressure, pulse pressure, mean arterial pressure, and heart rate). Additionally, RMS, PFT, and physical performance showed significant increases. Improvements were also observed in HRV, biochemical markers (fasting blood sugar and lipid profile), oxidative stress markers (catalase, superoxide dismutase, and malondialdehyde), and stress levels. In contrast, no significant changes were found in the control group. Conclusion Slow deep breathing exercises, as a non-pharmacological intervention, significantly improve cardiopulmonary function, physical performance, and various health markers in older adult patients with long COVID. This approach provides a valuable and accessible therapeutic option for this population.